2020
DOI: 10.1007/s11606-020-06297-w
|View full text |Cite
|
Sign up to set email alerts
|

Medical Multimorbidity, Mental Illness, and Substance Use Disorder among Middle-Aged and Older Justice-Involved Adults in the USA, 2015–2018

Abstract: BACKGROUND: Adults age ≥ 50 are among the fastest growing populations in correctional supervision and are medically underserved while experiencing unique health disparities. Community-living older adults, referred to as "justice-involved," are people who have been recently arrested, or are on probation or parole. Although medical complexity is common among incarcerated older adults, the occurrence of medical morbidity, substance use disorder (SUD), and mental illness among justice-involved older adults living … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 29 publications
0
11
0
Order By: Relevance
“…[11][12][13] In addition, this study found a higher prevalence of co-occurring mental illness, SUDs, and MM compared with those reported among non-veteran CLS-involved older adults in a national study. 3 While multimorbidity is common among older veterans and represents a high-cost patient population within the VHA system, 16 CLS-involved older veterans have unique health care needs because of the complex interplay between SUD, mental illness, and MM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13] In addition, this study found a higher prevalence of co-occurring mental illness, SUDs, and MM compared with those reported among non-veteran CLS-involved older adults in a national study. 3 While multimorbidity is common among older veterans and represents a high-cost patient population within the VHA system, 16 CLS-involved older veterans have unique health care needs because of the complex interplay between SUD, mental illness, and MM.…”
Section: Discussionmentioning
confidence: 99%
“…Our study found that being CLS involved was strongly associated with being diagnosed with a stimulant use disorder. Despite the high prevalence of methamphetamine use among CLS-involved older adults in general, 3 most research on SUD interventions for CLS populations focuses on alcohol or opioid use disorders. [17][18][19][20] Meanwhile, the prevalence of co-occurring opioid and methamphetamine use disorder is increasing sharply among veterans, 21 and methamphetamine use itself is associated with multimorbidity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, specific research that qualitatively examines subjective accounts of drug abuse among IOAs is lacking. This type of evaluation is critical given the complex and nuanced evidence regarding the exclusive characteristics of drug abuse among these individuals ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…As noted, limited studies have examined IOAs coping with drug abuse issues ( 15 ). Previous research has suggested that IOAs are atypical in their drug abuse habits ( 16 ), meaning that although IOAs tend to use more drugs than their age peers living in the community ( 6 ), their drug use is markedly lower than that of younger incarcerated individuals ( 17 ). In addition, alcohol abuse is the most prevalent substance used by IOAs ( 5 ), followed by opioids ( 18 ).…”
Section: Introductionmentioning
confidence: 99%